The Public Participation in the Prevention and Resolution of Drug Related Issues in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province - Yuwareungsri , Waraporn; Hombunma, Pannathorn (Journal of Dhamma for Life, 2025)
The purposes of this research were to: 1) to study level of cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University; 2) compare the cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University classified by their personal factors; and 3) provides guidelines for cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University. The sample group, obtained by stratified random sampling, consisted of 210 Students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University. The research instrument was a questionnaire of cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University with a reliability level at 0.92. Statistical analysis was performed in terms of frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, LSD test, The purposes of this research were to: 1) to study level of the public participation in the prevention and resolution of drug related issues in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province; 2) compare level of the public participation in the prevention and resolution of drug related issues in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province classified by gender, age, educational level, occupation, and monthly income; and 3) propose strategies to promote public participation in the prevention and resolution of drug related issues in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province. The sample group, obtained by quota sampling, consisted of 361 residents living in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province. The research instrument was a questionnaire of level of the public participation in the prevention and resolution of drug related issues in Lumphli Subdistrict, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province with a reliability level at 0.99. Statistical analysis was performed in terms of frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, LSD test, The research findings revealed as follows: 1) The level of public participation in drug prevention and solution in Lumpli Sub-district, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province, overall, is at a high level. The highest level of participation is participation in receiving benefits, followed by participation in operations, and the lowest level of participation is participation in decision-making; 2) People with different genders, occupations, and monthly incomes have different participation in drug prevention and solution in Lumpli Sub-district, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province, overall, with statistical significance at the 0.05 level; 3) There are 21 items on the guidelines for promoting public participation in drug prevention and solution in Lumpli Sub-district, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province, which are divided into 5 items on participation in decision-making, such as giving people an opportunity to attend meetings to find ways to prevent and solve drug problems in villages/communities; 6 items on participation in operations, such as raising awareness among people to help monitor drug problems in the community; 7 items on participation in receiving benefits, such as organizing a drug-free village project to make people feel safe in their lives; and 3 items on participation in evaluation, such as organizing a meeting to summarize the results of drug prevention and solution activities in the community to inform the community of progress, successes, and problems found. By giving the public an opportunity to express their opinions and suggest ways to improve.